Development and Validation of an Augmented Reality-Based Handout on the Kidney Excretory System for Grade XI Senior High School Students - Nanda Prafitasari, Aulya; Setyo Kurniawati, Lintang; Priantari, Ika; Wulandari, Siti; Alfan, Mochamad (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2026)
Biology learning at the senior high school level often struggles in explain abstract concepts, particularly the structure and function of the human excretory system. Reliance on conventional printed textbooks with static two-dimensional images may hinder students' understanding, leading to misconceptions and low learning motivation. This study aimed to develop and validate an augmented reality (AR)-integrated printed handout on the kidney excretory system material for Grade XI students at SMA Muhammadiyah Jember, Indonesia. The study employed a Research and Development approach using the ADDIE model. The handout was designed in Canva, and the three-dimensional AR kidney model was developed in Unity and accessed via barcode markers on students' smartphones. Product validity was assessed by two university lecturers and one biology teacher using a 30-item validation instrument. The product achieved an overall validity score of 85.28% and was categorized as very valid, indicating that it is feasible and pedagogically appropriate for biology learning. Pengembangan dan Validasi Handout Berbasis Augmented Reality pada Materi Sistem Ekskresi Ginjal untuk Siswa SMA Kelas XI ABSTRAK: Pembelajaran biologi di tingkat sekolah menengah atas sering menghadapi kesulitan dalam menjelaskan konsep-konsep abstrak, khususnya struktur dan fungsi sistem ekskresi manusia. Ketergantungan pada buku teks cetak konvensional dengan gambar dua dimensi statis dapat menghambat pemahaman siswa, sehingga menimbulkan miskonsepsi dan rendahnya motivasi belajar. Penelitian ini bertujuan untuk mengembangkan dan memvalidasi handout cetak terintegrasi augmented reality (AR) pada materi sistem ekskresi ginjal untuk siswa kelas XI di SMA Muhammadiyah Jember, Indonesia. Penelitian ini menggunakan pendekatan Research and Development dengan model ADDIE. Handout dirancang menggunakan Canva, sedangkan model ginjal AR tiga dimensi dikembangkan menggunakan Unity dan diakses melalui marker barcode pada telepon pintar siswa. Validitas produk dinilai oleh dua dosen universitas dan satu guru biologi menggunakan instrumen validasi 30 butir. Produk memperoleh skor validitas keseluruhan sebesar 85,28% dan dikategorikan sangat valid, yang menunjukkan bahwa media tersebut layak dan sesuai secara pedagogis untuk pembelajaran biologi.